Escalation of Visual Street Furniture Accentuation at Public Corridor of Baiturrahman Mosque in Putroe Phang Park - Rinal Mirsa; Muhammad Muhammad; Mega Aulia; Yenni Novianti (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2023)
The public corridor is the basic character of the road which represents a linear movement space, becomes a provision for circulation. The road corridor as a linear space is not only a circulation space, but as part of a community activity space that has the potential to increase and develop. The formulation of the problem in this study is how to identify street furniture in public corridors, visual accentuation of street furniture in public corridors and escalation of visual accentuation of street furniture in public corridors. Aims to find out how the escalation of the visual accentuation of street furniture. This study uses a quantitative method with a descriptive approach. The results obtained from this study are that the majority of respondents to street furniture that are more attractive and prominent are decorative lights. However, street furniture that doesn't stand out is the sidewalk. Things that must be escalated are sidewalks and facilities with pedestrian paths. To create a good pedestrian path, it must have complete, safe and comfortable criteria.